Adverse pregnancy outcomes related to preterm cesarean delivery. (March 2019) - Kino, Tamina; Yamamoto, Yuriko; Saigusa, Yusuke; Aoki, Shigeru; Miyagi, Etsuko
Abstract: Objective: Cesarean delivery at a preterm gestational age has been related to maternal complications such as bleeding and infection. However, previous reports are conflicting, and there is no consensus on the matter. We aimed to clarify the adverse effect of preterm cesarean delivery with an emphasis on maternal bleeding. Study design: We conducted a retrospective study comparing the frequency of maternal adverse outcome between preterm emergency cesarean delivery and term emergency cesarean delivery. Nine hundred and forty seven preterm cases and 1056 full-term cases were included in the study. We analyzed the frequency of abnormal bleeding defined as 1500 mL or more as primary outcome, blood transfusion rate, and rate of postoperative administration of antibiotics as secondary outcome. Logistic regression analysis was performed for confounding variables; age at delivery, primiparity, obesity, prior history of uterine surgery, abnormal placental position, abnormal glucose tolerance, hypertension during pregnancy, early rupture of membranes, and general anesthesia use during operation. As secondary analysis, to study the effects of method of incision, we compared adverse outcomes among classical cesarean delivery, inverted T incision, and upper segment incision within preterm emergency cesarean delivery. Results: Preterm cesarean delivery had significantly higher rates of abnormal bleeding, transfusion and use of antibiotics than term cesarean delivery. Among the preterm delivery, classical incision was related to increased rate of blood transfusion and need for antibiotic treatment. Conclusion: Preterm cesarean delivery increases the risk of maternal bleeding. This should be considered especially in the setting of early preterm birth.